TINJAUAN SUMBER-SUMBER HUKUM DAN KAITANNYA DENGAN PERKEMBANGAN HUKUM KONTRAK INTERNASIONAL - Dery Ariswanto (IAIN Ambon, 2022)
This paper is used to elaborate on the sources of law in international contracts and their relation to the development of international contract law. An international contract is an agreement involving two or more countries and the contract can occur between countries, between state and private, or exclusively between private parties. While the sources used as a reference in the application of international cooperation include international treaties, customary international law, general legal principles, judgments and judicial bodies, contracts/ agreements, and national law. Contract activities or international agreements will continue to grow and develop in a better direction if the sources in the international contract law above are fully implemented. The development of contract law in the international world is marked by the growth of soft-law and hard-law, for example with the existence of UNIDROIT, CISG, UNCITRAL and agreements or other legal sources like that which have been able to improve international contract arrangements and are able to bring harmony to facilitate business transactions between countries in the international world.